Sistem Pendukung Keputusan Seleksi Penerima Beasiswa Menerapkan Metode Weighted Aggregated Sum Product Assessment (WASPAS) - Silalahi, Natalia; Tambusai, Robbi; Mesran, Mesran; Sarwandi, Sarwandi; Siagian, Meryance V (TIN: Terapan Informatika Nusantara, 2021)
Scholarship is financial assistance given to every student or student with the aim of helping the education that will be taken. Scholarships are usually given by government agencies, foundations, or private companies or state-owned companies. To determine scholarship recipients, there are many criteria that must be possessed by individuals as a society to get scholarships. Each school must have criteria to determine who will be selected to receive the scholarship. The distribution of scholarships is carried out by several agencies to help someone who is underprivileged or has high achievements during their studies. To determine the scholarship recipients, several methods can be used, in this case the author uses the Weight Aggreated Sum Product Assessment (WASPAS) method for scholarship recipients to students. In the WASPAS method, it is considered appropriate for the selection of scholarship recipients because the WASPAS method will carry out a chaining process based on attributes with a weight for each attribute, then a ranking process is carried out which will determine the optimal alternative for the selection of scholarship recipients